A multibelief analytic hierarchy process and nonlinear programming approach for diversifying product designs: Smart backpack design as an example. (May 2020) - Lin, Yu-Cheng; Chen, Toly
Owing to the cost constraint, it is difficult to incorporate all critical features into a single product design. To deal with this issue, analytic hierarchy process is a well-known method that compares the relative priorities of critical features. This study aims to illustrate that the judgment of a designer can be used to generate multiple diversified product designs. To this end, this study proposed a multibelief analytic hierarchy process and nonlinear programming approach. In the proposed methodology, a decision maker's judgment matrix is decomposed into several single-belief judgment matrices that are more consistent than the original judgment matrix and represent diversified points of view regarding the relative priorities of factors. To this end, a nonlinear programming model is established and optimized. The proposed methodology was applied to a smart backpack design problem. It was concluded that a designer's judgment was often inconsistent, which was ignored in the conventional analytic hierarchy process method but could be employed to diversify product designs.